2020
DOI: 10.1177/1077558720960326
|View full text |Cite
|
Sign up to set email alerts
|

Inside the Black Box of Improving on Nursing Home Quality Measures

Abstract: Nursing Home Compare (NHC) reports quality measures (QMs) for nursing homes (NHs) as part of its 5-star rating system. Most of the QMs are based on facility self-reported data, prompting questions about their validity. To better understand how NHs interact with the QMs, we used qualitative methods, including semistructured interviews with NH personnel ( n = 110), NH provider association representatives ( n = 23), and observations of organizational processes in 12 NHs in three states. We found that most NHs are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…A study of five common Medicare hospital diagnoses found that SNF days for patients with a stroke declined immediately after the BBA, whereas overall use of inpatient rehabilitation and long‐term hospital care increased 15 . Qualitative research has revealed that SNFs did engage in patient selection strategies to admit fewer high‐risk patients under PPS 25 . However, SNF length of stay was relatively unchanged compared to the pre‐PPS period, which was unsurprising as the SNF PPS reimbursed SNFs on a per diem and not an episode basis 8,18 .…”
Section: The Balanced Budget Act and Pps For Skilled Nursing Facilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of five common Medicare hospital diagnoses found that SNF days for patients with a stroke declined immediately after the BBA, whereas overall use of inpatient rehabilitation and long‐term hospital care increased 15 . Qualitative research has revealed that SNFs did engage in patient selection strategies to admit fewer high‐risk patients under PPS 25 . However, SNF length of stay was relatively unchanged compared to the pre‐PPS period, which was unsurprising as the SNF PPS reimbursed SNFs on a per diem and not an episode basis 8,18 .…”
Section: The Balanced Budget Act and Pps For Skilled Nursing Facilitiesmentioning
confidence: 99%
“…15 Qualitative research has revealed that SNFs did engage in patient selection strategies to admit fewer high-risk patients under PPS. 25 However, SNF length of stay was relatively unchanged compared to the pre-PPS period, which was unsurprising as the SNF PPS reimbursed SNFs on a per diem and not an episode basis. 8,18 Additional early process changes incentivized by the SNF PPS included a move toward bringing therapy services in-house rather than employing contract therapy companies, allowing SNFs more control over the cost of therapy services as they navigated uncertainty.…”
Section: Snf Pps Incentives and Concernsmentioning
confidence: 99%
“…When (Lee & Wendling, 2004 ) surveyed Kansas' NHs about the extent of their quality improvement program, they concluded that few NHs had systematic quality improvement programs in place. More recently, Davila et al ( 2021 ) found that the majority of NH directors reported carrying out “data‐focused strategies” to improve quality outcomes. However, methodological differences make comparisons with our data difficult.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, the federal government requires all Medicare-or Medicaid-certified nursing homes (about 15,000 in total) to routinely report detailed resident demographic, health, functioning, and treatment information using the uniform MDS (which ironically contains more than 400 data items) for resident assessment, care planning, payment, and public reporting purposes. Despite the enormous costs of collecting these data as well as developing and maintaining numerous nursing-home quality measures (Mor 2011), the impact of using these data for improving quality and consumer experience is mixed (Davila et al 2021;Konetzka et al 2022). In health care more broadly, between 2008 and 2018, the federal government invested more than US$1.3 billion in quality measure development, with approximately 2,300 measures developed, of which 788 (34 percent) are being used in government-mandated quality, reporting, and payment programs (Wadhera et al 2020).…”
Section: Older Adult Care Needs-strengthening Assessment and Quality ...mentioning
confidence: 99%